Gentleman Jack. The complete first season [videorecording (DVD)] - Wainwright, Sally, 1964-; Jones, Suranne, 1978-; Rundle, Sophie; Cavaliero, Rosie (HBO Home Entertainment, 2019)
Anne Lister returns to Halifax, West Yorkshire in 1832, determined to transform the fate of her faded ancestral home Shibden Hall.